Persistence and nominal inertia in a generalized Taylor economy: how longer contracts dominate shorter contracts - Huw Dixon; Engin Kara (European Central Bank (ECB), 2005)
In this paper we develop the Generalized Taylor Economy (GTE) in which there are many sectors with overlapping contracts of different lengths. In economies with the same average contract length, monetary shocks will be more persistent when longer contracts are present. We are able to solve the puzzle of why Calvo contracts appear to be more persistent than simple Taylor contracts: it arises because of the distribution of contract lengths. When we choose a GTE with the same distribution of completed contract lengths as the Calvo, the economies behave in a similar manner.
Keywords: E50; E24; E32; E52; 330; Calvo; Persistence; Taylor contract; Preisrigidität; Geldpolitik; Schock; Dynamisches Gleichgewicht; Theorie